Long-Term Effects of Maternal Deprivation on Cholinergic System in Rat Brain. (10th March 2014) - Marković, Branka; Radonjić, Nevena V.; Aksić, Milan; Filipović, Branislav; Petronijević, Nataša
Abstract : Numerous clinical studies have demonstrated an association between early stressful life events and adult life psychiatric disorders including schizophrenia. In rodents, early life exposure to stressors such as maternal deprivation (MD) produces numerous hormonal, neurochemical, and behavioral changes and is accepted as one of the animal models of schizophrenia. The stress induces acetylcholine (Ach) release in the forebrain and the alterations in cholinergic neurotransmitter system are reported in schizophrenia. The aim of this study was to examine long-term effects of maternal separation on acetylcholinesterase (AChE) activity in different brain structures and the density of cholinergic fibers in hippocampus and retrosplenial (RS) cortex. Wistar rats were separated from their mothers on the postnatal day (P) 9 for 24 h and sacrificed on P60. Control group of rats was bred under the same conditions, but without MD. Brain regions were collected for AChE activity measurements and morphometric analysis. Obtained results showed significant decrease of the AChE activity in cortex and increase in the hippocampus of MD rats. Density of cholinergic fibers was significantly increased in CA1 region of hippocampus and decreased in RS cortex. Our results indicate that MD causes long-term structure specific changes in the cholinergic system.